Pengaruh Digital Literacy dan Technology Acceptance Model Terhadap Keputusan Donatur Membayar Zakat, Infaq, Sedekah (ZIS) Melalui Aplikasi Digital - Arip Nugraha, Jujun (LPPM IAIT, 2023)
The purpose of this study was to determine the effect of the two Digital Literacy and Technology Acceptance Model variables on Donors' decisions in paying ZIS through Digital Applications at LAZISMU Tasikmalaya City. This study used a quantitative approach which was processed in SPSS involving 20 respondents. The method used is Purposive Sampling with the criteria of Digital Application users who are Donors from LAZISMU Tasikmalaya City. For data obtained using an online questionnaire using a Likert scale of 1 to 5, with statements that strongly agree to disagree. The results of this study indicate that there is a positive and significant influence between the Digital Literacy and Technology Acceptance Model variables on donors' decisions in paying ZIS through Digital Applications at LAZSIMU Tasikmalaya City.